A high‐stress shelly fauna associated with sponge mud‐mounds in the Coniacian Arnager Limestone of Bornholm, Denmark. (1st August 2018) - Svennevig, Kristian; Surlyk, Finn
Abstract : The benthic macrofaunas of the Upper Cretaceous chalk of NW Europe show characteristically high species‐richnesses and commonly high densities. They are predominated by bivalves, brachiopods, polychaetes, echinoids, crinoids, asteroids, sponges and towards the end of the Cretaceous also by bryozoans. The mound‐bedded chalk of the Coniacian Arnager Limestone on the island of Bornholm in the Baltic Sea, Denmark, differs from this general picture. It was deposited on a small fault block adjacent to the main Bornholm block, which was emerged during much of the Mesozoic and thus occupied a much more proximal position than most other Upper Cretaceous chalks in NW Europe. The Arnager Limestone contains a unique, exceptionally rich and well‐preserved fauna of mainly hexactinellid, lyssacinosan sponges. The low mud‐mounds are interpreted as formed by baffling and trapping of fine sediment particles by the dense sponge thickets. In contrast, the associated shelly fauna is unusually sparse, of very low richness and extremely low density, except for inoceramid bivalves. It represents a strongly depauparated version of the shelly faunas of contemporaneous chalks in NW Europe. The rare specimens of non‐inoceramid shelly species are interpreted to represent occasional successful spatfalls of benthic species from the deeper‐water chalk farther offshore in the Baltic area. The sponge mud‐mounds of the Arnager Limestone show remarkable resemblances with modern sponge mounds recently discovered on the continental shelf of western Canada. They form an important link between the well‐known older Mesozoic sponge mud‐mounds or 'reefs' and the modern mounds and are among the youngest examples of Mesozoic sponge mounds.